Kveekarien usko ja hiljaisuuden kokemus = The faith of the Quakers and the experience of silence - Alhonsaari, Antti (Studia missiologica et oecumenica Fennica, 1993)
Engl. Zsfassung u.d.T.: The faith of the Quakers and the experience of silence